First-principles predictions of the structural, electronic, optical and elastic properties of the zintl-phases AE3GaAs3 (AE = Sr, Ba) - Khireddine, A.; Bouhemadou, A.; Alnujaim, S.; Guechi, N.; Bin-Omran, S.; Al-Douri, Y.; Khenata, R.; Maabed, S.; Kushwaha, A.K. (Solid state sciences, 2021)
We report results of a detailed first-principles study of physical parameters associated with the structural, electronic, optical and elastic properties of the ternary gallium-arsenides Sr3GaAs3 and Ba3GaAs3. Calculated equilibrium structural parameters are in excellent agreement with the available experimental counterparts, providing evidence of the reliability of the reported results. Monocrystalline elastic constants are numerically estimated and analyzed. From the monocrystalline elastic constants, a set of related properties, viz. mechanical stability, anisotropic sound velocities, polycrystalline elastic properties, including bulk modulus, shear modulus, Young's modulus, Poisson's ratio, average sound velocity and Debye temperature, are deduced. Crystal direction dependences of the linear compressibility and Young's modulus are analyzed and visualized by plotting their spatial distributions. From analysis of the energy band dispersions, it is found that the title compounds are semiconductors with direct band gaps positioned in the visible sunlight spectrum in the energy window 1.271–1.285 eV. Origins of the electronic states composing the energy bands are determined using the PDOS diagrams. Eﬀective masses of holes and electrons are numerically evaluated at the valence band and conduction band extremes towards the three major crystalline directions. Anisotropies of the hole and electron effective masses are visualized by plotting their dependencies on the crystalline direction. Frequency-dependent linear optical parameters are predicted in an energy window from 0 eV to 14 eV for incident electromagnetic radiation polarized parallel to the three principal crystalline directions. [Display omitted] •The fundamental physical properties of Sr3/Ba3GaAs3 are explored.•They are mechanically stable with moderate stiffness and a significant elastic anisotropy.•They are direct band gap semiconductors with mixed covalent-ionic bond characters.•They possess a high absorption band from the visible spectrum to Near-UV.